VD_FINDINFO Pron / 2013 / 58 vom 4. März 2013 - VD Tribunal cantonal (2013)
TRANSACTION JUDICIAIRE, HONORAIRES, AVOCAT D'OFFICE | 106 al. 2 CPC (CH), 109 al. 2 let. a CPC (CH), 241 CPC (CH), 2 al. 1 RAJ